2017
DOI: 10.1007/s11896-017-9234-0
|View full text |Cite
|
Sign up to set email alerts
|

Is the Public Willing to Help the Nigerian Police During the Boko Haram Crisis? A Look at Moderating Factors

Abstract: This paper sought the opinion of 200 Nigerians on their willingness to cooperate with the police during the Boko Haram crisis. Public perceptions of police effectiveness during the crisis, residence location, gender and religious affiliation were used as moderators. Data was analysed using an explanatory factor analysis and structural equation modelling. Results indicated a strong association between perceived effectiveness and willingness to report to the police with respondents who question the effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…Police corruptive and abusive behaviors and low effectiveness in criminal investigation have led to poor police–community relations exemplified by uncooperative public attitudes toward and fear and mistrust of the police (Zumve, 2012). A recent study showed that people who cast doubt on the Nigerian police’s effectiveness were less likely to report criminal activity about the terrorist group of Boko Haram (Elntib et al, 2018). A strained relationship between the police and the public makes community policing a failed reform in Nigeria (Zumve, 2012).…”
Section: Predicting Organizational Commitment Among Police Officersmentioning
confidence: 99%
“…Police corruptive and abusive behaviors and low effectiveness in criminal investigation have led to poor police–community relations exemplified by uncooperative public attitudes toward and fear and mistrust of the police (Zumve, 2012). A recent study showed that people who cast doubt on the Nigerian police’s effectiveness were less likely to report criminal activity about the terrorist group of Boko Haram (Elntib et al, 2018). A strained relationship between the police and the public makes community policing a failed reform in Nigeria (Zumve, 2012).…”
Section: Predicting Organizational Commitment Among Police Officersmentioning
confidence: 99%
“…A kriminológiai szakirodalom hosszú ideig evidensnek vette a rendőrségbe vetett bizalom és a feljelentési hajlandóság közötti kapcsolatot is (Kääriäinen & Sirén, 2011), korábban azonban csak szórványosan kutatták az összefüggést empirikus módszerekkel (Fishman, 1979;Bennett & Wiegand, 1994;Sunshine & Tyler, 2003;Goudriaan, Lynch & Nieuwbeerta, 2004;Goudriaan, Wittebrood & Nieuwbeerta, 2006;Davis & Hendricks, 2007;Tyler & Fagan, 2008;Tankebe, 2009;Slocum, Taylor, Brick & Esbensen, 2010;Tyler, Schulhofer & Huq, 2010). Az elmúlt öt-tíz évben azonban egyre több kutatás jelent meg a témát vizsgálva (Kääriäinen & Sirén, 2011;Murphy & Cherney, 2011;Kochel, Parks & Mastrofski, 2013;Semukhina, 2014;Murphy & Barkworth, 2014;Sargeant, Murphy & Cherney, 2014;Tsushima & Hamai, 2015;Kruger et al, 2016;Tyler, 2001;Tankebe, 2016;Van Damme, 2016;Karakus, 2017;Khondaker, Wu & Lambert, 2017;Murphy et al, 2017;Slocum, 2018;Wiedlitzka, Mazerolle, Fay-Ramirez & Miles-Johnson, 2018;Boateng, 2018;Murphy & Mazerolle, 2018;Griffiths, 2018;Elntib, Nass, Ioannou, Ryan & Christiansen, 2018;Özaşçilar, Narli, N & Öztürk, 2018;Sun, Li, Wu & Hu, 2018;Kwak, Dierenfeldt & McNeeley, 2019;Rengi...…”
Section: Bevezetésunclassified
“…Perhaps, an easy way to gauge the outlook of police-community relations in Nigeria is to consider the difficulty of entrenching community policing in modern-day Nigerian policing (Zumve, 2012). People who cast doubt on the Nigerian police's effectiveness were less likely to report criminal activity about the terrorist group of Boko Haram (Elntib et al, 2018), limiting the police's efforts in trying to build up community-based, effective crime prevention programs.…”
Section: Policing In Nigeriamentioning
confidence: 99%